Physical and chemical characterization of Lopburi clay before and after calcination - P. Chomyen (2020)
© Published under licence by IOP Publishing Ltd. Supplementary cementitous materials (SCMs) may be used as a substitution of Portland cement to reduce CO2 emissions in the cement industry. One of promising Supplementary cementituous materials for practical use in the construction industry is calcined clay. Clay must be calcined to form high reaxtivity pozzolanic materials from mineral addition known as amorphous metakaolin (AS2). Calcined clay may be used to improve mechanical properties, durability and some characteristic. This research aimed to study clay mineralogy and chemical composition of Lopburi clay in Thailand. Physical and chemical characterizations of Lopburi clay before and after calcination were investigated using X-Ray Diffraction, Qualitative X-Ray Diffraction (QXRD), Scanning Electron Microscopy (SEM) and X-Ray Fluorescene. The results showed that Lopburi clay main major oxides aed silicon dioxide (SiO2), alumina oxide (Al2O3) and iron oxide (Fe2O3) furthermore, Lopburi clay is kaolinite clay.